Foot clearance measurement using ultrasound wireless network - Lim, Norvin Hong Yao (2016)
Falling is very common especially when we are facing aging population, falls happen more commonly in the elderly due to the weakening of the leg muscles. Falls cannot be look lightly on, it can cause undesirable health problems. Foot clearance measurement have become a more popular topic for researchers, so that deeper knowledge can be known between gait and falls. Technologies advancement have allow us to collect foot clearance data via many ways, each have its advantages and disadvantages, therefore in this project, due to cost limitation but relative accurate measuring and tracking system, we have chosen to use ultrasound wireless network. A control module together with four receiver (Anchors) will be placed in fixed position, the only moveable module is the transmitter module, so to reduce position error. MATLAB programming will be used to further analyze the collected data. Extended Kalman Filters will be used during the analyzing of data to reduce noise which will cause the readings to be not accurate.